2022
DOI: 10.21608/jappmu.2022.132115.1035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emulsified and Nano-Emulsified Essential Oils Blend on Performance and Meat Characteristics of Weaned Mountain Rabbits

Abstract: The study aimed to evaluate the effects of adding emulsified or nano-emulsified essential oil blend (garlic, pomegranate, tea tree essential oil), at the same level to weaned Mountain rabbits diet, on their growth performance, blood components, meat analysis, meat fatty acids and immunity indices. A total of forty-five weaned Mountain rabbits, were assigned randomly to 3 similar groups. Rabbits in the 1 st group (T1, the control) were fed only concentrate feed mixture. The 2 nd group (T2) and 3rd group (T3) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The above results indicate that the better growth performance of the NCEO-supplemented rabbits was achieved by enhancing the defeasibility of nutrients, which provide available energy for growth and heat dissipation from the body. In this study, the NCEO300 and NCEO600 groups had a higher FBW, ADG, SGR, and PI and a lower FCR than the control and other treated groups, which is in general agreement with the findings of former studies [ 36 , 40 ]. They reported that the dietary supplementation of rabbit diets with nano-emulsified essential oils enhanced their growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 93%
“…The above results indicate that the better growth performance of the NCEO-supplemented rabbits was achieved by enhancing the defeasibility of nutrients, which provide available energy for growth and heat dissipation from the body. In this study, the NCEO300 and NCEO600 groups had a higher FBW, ADG, SGR, and PI and a lower FCR than the control and other treated groups, which is in general agreement with the findings of former studies [ 36 , 40 ]. They reported that the dietary supplementation of rabbit diets with nano-emulsified essential oils enhanced their growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 93%
“…This can be confirmed by the findings of our study as the MEONE-supplemented rabbits had better FBW, ADG, PI, and FCR compared to the control rabbits, recording the highest significant values with 400 mg MEONE/kg diet. The current results coincide with the results of Abdelhadi et al [41], who showed significant effects of adding essential oils and nanoemulsified essential oils (garlic, pomegranate, and tea tree essential oils) to rabbit diets on growth performance and feed utilization. The improved growth performance in this study could be linked to the enhanced feed utilization and the nutrients digestibility.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, we have focused on studying the changes in these two pathways in heat-stressed and MEONE-supplemented rabbits. Giving in mind that essential oils can alleviate the negative effects of HS through controlling these two major cells damaging pathways, oxidative and inflammatory pathways [6,14,41,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The n-6/n-3 ratio can increase the risk of cancer and heart disease, especially blood clots that lead to heart attacks [ 31 ]. Researchers analyzing rabbit meat found that n-6/n-3 values varied significantly and ranged from 3.29 to 25 [ 32 34 ]. This result is in agreement with our results.…”
Section: Resultsmentioning
confidence: 99%